Utrata wartości aktywów w ramach przepisów prawa rachunkowego obowiązujących na Słowacji - Tumpach, Milos; Juhaszova, Zuzana (Impairment of Assets in the Legal Framework of Accounting in Slovakia, 2005)
Accounting for impairment of assets is one of the paramount aspects of the true and fair view.This is even truer in these days, when the risks and uncertainties become the only certain things in thecontemporary world of business. Even though the basic idea might be considered as a commonplace,the practice might be quite different in various areas of the world. Thus it is one of the most importantvirtues of the International Accounting Standards - to serve as a Trojan horse of the best accountingideas send to a fortress of somewhat conservative tribe of accountants. However, unlike the history,there is no place for a single winner. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 197-201